Pott’s disease associated with bilateral psoas abscess: a case report on surgical management using anterior approach - Durgut, Fatih; Gulec, Ali; Eravsar, Ebubekir; Odabasi, Egemen (Journal of the Pakistan Medical Association, 2022)
Pott’s disease may accompany psoas abscesses, but bilateral psoas abscess is rarely encountered. Computerised Tomography (CT) is the gold standard for the diagnosis of psoas abscesses. Treatment of psoas abscess usually involves drainage of abscess and antibiotic therapy. CT and USG-guided catheters are often utilised for abscess drainage. In cases where neurological symptoms are observed, open surgery may be required. Pott’s disease accompanied by bilateral psoas abscess was detected in a 21-year-old male patient who was admitted to the clinic with complaints of low back pain and weakness in his left leg at the Selcuk University, Turkey, in 2018. The reason for the development of neurological deficit only on the left side was the compression of the nerve roots by the abscess tissue. The patient underwent debridement and anterior instrumentation with an anterior approach. In the postoperative follow-up it was observed that the patient’s complaints were relieved. —Continue